The knowledge economy, hub airports and accessibility. A location based perspective. - Sven Conventz; Alain Thierstein (European Regional Science Association (ERSA), 2011)
The airplane is gradually creating a completely new spatial pattern as did other kinds of transportation modes in the past. Successively, international airports have gone through a morphogenesis from original pure infrastructure facilities into multimodal and multilayered spatial growth poles and center of competences. Landside infrastructure investments have converted airports and their hinterland into spaces of highest accessibility. The airports unique locational advantages and the growing segment of non-aviation activities on the part of the airport operators have made airports an advantageous business location for knowledge-intensive industries. At the same time airports have become a crucial asset for city-regions especially those competing on a European or international spatial level for future-oriented enterprises and highly skilled employees. The paper asks about the general interplay between airports, air transport and the knowledge economy. What are the contributions of the knowledge economy that explain the economic effects of airports on the spatial structure? What kinds of knowledge economy linked locational patterns have already emerged around airports? What is their spatial relationship to more traditional locations for example within the core cities? Why does an array of knowledge-based companies relocate their business activities at spaces of highest accessibility such as international airports? This paper analyzes aviation induced spatial patterns and processes of specialization around European airports, especially around those with hub function. First results show that airports and their vicinities have become attractive sites for real estate developments and property-led capital accumulation. Locations directly at or close by international airports are notably in demand among highly globalized sectors characterized by their need for frequent face-to-face interaction, high value products and services. As the traditional role of airports is redefined a new spatial quality and entity within the city regions is evolving.
Keywords: 330